Duration of Environmental Enrichment Determines Astrocyte Number and Cervical Lymph Node T Lymphocyte Proportions but Not the Microglial Number in Middle-Aged C57BL/6 Mice - Singhal, Gaurav; Morgan, Julie; Jawahar, Magdalene C.; Corrigan, Frances; Jaehne, Emily J.; Toben, Catherine; Manavis, Jim; Hannan, Anthony J.; Baune, Bernhard T. (Frontiers in Cellular Neuroscience, 2020)
Environmental enrichment (EE) has been shown to modulate behavior and immunity. We recently reported that both short and long-term EE enhance baseline locomotion and alleviate depressive-like behavior, but only long-term EE affects locomotion adversely in a threatening environment and enhances anxiety-like behavior in middle -age mice. We have now investigated whether the observed changes in behavior after short- and long-term EE were associated with underlying immune changes. Hence, at the end of behavioral testing, mice were sacrificed, and brains and cervical lymph nodes were collected to investigate the differential effects of the duration of EE (short- and long-term) on the number of immunopositive glial cells in the dentate gyrus, CA1, CA2 and CA3 regions of the hippocampus and proportions of T cell subsets in the cervical lymph nodes using immunohistochemistry and flow cytometry, respectively. EE, regardless of duration, caused an increase in microglia number within the dentate gyrus, CA1 and CA3 hippocampal regions, but only long-term EE increased astrocytes number within the dentate gyrus and CA3 hippocampal regions. A significantly higher proportion of CD8+ naive T cells was observed after long-term EE vs. short-term EE. No significant differences were observed in the proportion of central memory and effector memory T cells or early activated CD25+ cells between any of the test groups. Our results suggest that EE, irrespective of duration, enhances the numbers of microglia, but long-term EE is required to modify astrocyte number and peripheral T cell proportions in middle-aged mice. Our findings provide new insights into the therapeutic effects of EE on various brain disorders, which may be at least partly mediated by glial and neuroimmune modulation.